(3Gdbhd GdeNJUQ aj YdGeGJ GdegOi GdefJXQs - (3CMeO Hf eMeO Hf Ydj Hf nMnLQ GdngrjnJej GdSYOj GdCfUGQj, TgGH GdOjf TjN GdESdGe, CHh GdYHGS,J (B974 (3g` s
(3ChdgG (B:s
(3hHYO , agPG cJGH dbjJg Gdbhd GdeNJUQ ai YdGeGJ GdegOi GdefJXQ CPcQ ajg eG EWdYJ Ydjg ef YdGeGJg haVGFdg hNUhUjGJg s
(3BNQgG (B:s
(3aEf GdegOi ajg JCdjaGJ , hcPG GdOLGd , hcPG HbjI GdBjGJ hdcfi EbJUQJ gfG Ydi eG dGHO efg hGdMeO ddg Je Pdc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdYfGhjjf hGdcdeGJ HGdMeQI s
(3Ydi ghGeTgG JYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJhMjO hGdedd hGdfMds